Electrocardiographic features of immune checkpoint inhibitor associated myocarditis. Issue 3 (2nd March 2021) - Zlotoff, Daniel A; Hassan, Malek Z O; Zafar, Amna; Alvi, Raza M; Awadalla, Magid; Mahmood, Syed S; Zhang, Lili; Chen, Carol L; Ederhy, Stephane; Barac, Ana; Banerji, Dahlia; Jones-O'Connor, Maeve; et al.
Abstract : Background: Myocarditis is a highly morbid complication of immune checkpoint inhibitor (ICI) use that remains inadequately characterized. The QRS duration and the QTc interval are standardized electrocardiographic measures that are prolonged in other cardiac conditions; however, there are no data on their utility in ICI myocarditis. Methods: From an international registry, ECG parameters were compared between 140 myocarditis cases and 179 controls across multiple time points (pre-ICI, on ICI prior to myocarditis, and at the time of myocarditis). The association between ECG values and major adverse cardiac events (MACE) was also tested. Results: Both the QRS duration and QTc interval were similar between cases and controls prior to myocarditis. When compared with controls on an ICI (93±19 ms) or to baseline prior to myocarditis (97±19 ms), the QRS duration prolonged with myocarditis (110±22 ms, p<0.001 and p=0.009, respectively). In contrast, the QTc interval at the time of myocarditis (435±39 ms) was not increased compared with pre-myocarditis baseline (422±27 ms, p=0.42). A prolonged QRS duration conferred an increased risk of subsequent MACE (HR 3.28, 95% CI 1.98 to 5.62, p<0.001). After adjustment, each 10 ms increase in the QRS duration conferred a 1.3-fold increase in the odds of MACE (95% CI 1.07 to 1.61, p=0.011). Conversely, there was no association between the QTc interval and MACE among men (HR 1.33, 95% CI 0.70 to 2.53, p=0.38) or women (HR 1.48, 95% CI 0.61 to 3.58, p=0.39). Conclusions: The QRS duration is increased in ICI myocarditis and is associated with increased MACE risk. Use of this widely available ECG parameter may aid in ICI myocarditis diagnosis and risk-stratification.